2021
DOI: 10.1016/j.ejca.2021.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of high-dose lanreotide autogel in patients with progressive pancreatic or midgut neuroendocrine tumours: CLARINET FORTE phase 2 study results

Abstract: Introduction: This prospective, single-arm, phase 2 study assessed the efficacy and safety of lanreotide autogel (LAN) administered at a reduced dosing interval in patients with progressive neuroendocrine tumours (NETs) after LAN standard regimen. Methods: Patients had metastatic or locally advanced, grade 1 or 2 midgut NETs or pancreatic NETs (panNETs) and centrally assessed disease progression on LAN 120 mg every 28 days. They were treated with LAN 120 mg every 14 days for up to 96 weeks (midgut cohort) or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 23 publications
0
46
0
2
Order By: Relevance
“…6 In the CLARINET FORTE study, only 22.7% of the PanNET patients had a CgA level > ULN. 7 For non-functional PanNET pancreatic polypeptide (PP) could be used to assist in the diagnosis of the disease. [8][9][10] The sensitivity for PP in metastatic disease is in the range 50-80%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In the CLARINET FORTE study, only 22.7% of the PanNET patients had a CgA level > ULN. 7 For non-functional PanNET pancreatic polypeptide (PP) could be used to assist in the diagnosis of the disease. [8][9][10] The sensitivity for PP in metastatic disease is in the range 50-80%.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis from the CLARINET study demonstrated that, at the time of diagnosis, only 49% and 26% of patients with PanNET had a higher than upper limit of normal (ULN) levels of CgA and 5‐HIAA, respectively 6 . In the CLARINET FORTE study, only 22.7% of the PanNET patients had a CgA level > ULN 7 . For non‐functional PanNET pancreatic polypeptide (PP) could be used to assist in the diagnosis of the disease 8–10 .…”
Section: Introductionmentioning
confidence: 99%
“…Some important clinical studies, including the PROMID[ 84 ] and CLARINET[ 85 ] trials, have demonstrated a significant efficacy of SSA in the control of tumor growth in patients with metastatic GEP-NETs. A recent CLARINET FORTE phase 2 clinical trial further supports the clinical benefit of the SSA lanreotide autogel (LAN), which led to significantly improved progression-free survival (PFS) and disease control rate in patients with GEN-NETs, especially in cases with a Ki67 index ≤ 10%[ 86 ]. In addition to SSA[ 87 ], novel therapeutic approaches, including PRRT, targeted therapy, and immunotherapy, have demonstrated promising clinical benefits[ 88 - 90 ].…”
Section: Novel Therapeutic Approachesmentioning
confidence: 99%
“…Although not routine, emerging data suggest that treatment with SSAs may be appropriate beyond progression with dose intensification. 15,50 In short, low-volume disease presents a unique challenge given a lack of data to guide therapy decisions and the potential for toxicities in patients who might otherwise have a relatively good prognosis.…”
Section: Low-volume Diseasementioning
confidence: 99%